Effects of the cross-talk between PARP12/PARP13 and nonsense mediated RNA decay pathway on RNA stability and replication of SARS-CoV-2 - Lokugamage, Nandadeva; Choudhuri, Subhadip; Rayavara, Kempaiah; Tseng, Chien-Te; Makino, Shinji; Garg, Nisha Jain (Frontiers in Virology, 2025)
BackgroundNonsense-mediated mRNA decay (NMD) pathway recognizes the mRNAs of host and cytoplasmic pathogens harboring aberrant features and targets them for degradation. Poly(ADP-ribose) polymerases (PARPs) superfamily consists of 17 members, among which macrodomain and zinc finger PARPs function as regulators of RNA metabolism and transcription. In this study, we investigated whether crosstalk between NMD and PARPs regulates SARS-CoV-2 RNA stability and viral infection.MethodsTransgenic mice (hACE2tg) expressing human angiotensin-converting enzyme 2, and human alveolar epithelial cells (Calu-3ACE2+, A549ACE2+), in which the expression of NMD factors and PARPs was modulated by molecular approaches were used for various studies.ResultsWe found that NMD pathway targets endogenous and exogenous aberrant transcripts in human lung epithelial cells. Upon SARS-CoV-2 infection, the expression of NMD factors, up-framshift 1 and 2 (UPF1/UPF2) was decreased while PARP12 and PARP13 were significantly increased in Calu-3ACE2+ and A549ACE2+ cells and lung tissues of hACE2tg mice. Depletion of PARP12/PARP13 using target-specific (vs. scrambled) siRNAs significantly enhanced the stability of NMD targeted endogenous and exogenous aberrant transcripts and SARS-CoV-2 subgenomic S, E, M, and N mRNAs in A549ACE2+ cells, like what was noted in siUPF1/siUPF2-transfected lung epithelial cells. Conversely, overexpression of PARP12/PARP13 enhanced the NMD-dependent degradation of aberrant transcripts and SARS-CoV-2 subgenomic and genomic RNAs. Further, overexpression of PARP12/PARP13 had a dose-dependent effect in enhancing the anti-viral NMD activity and suppression of SARS-CoV-2 replication in infected cells.ConclusionWe conclude that PARP12/PARP13 synergize with NMD pathway to regulate the viral mRNA stability and replication of SARS-CoV-2.